ANALISIS DAYA SAING EKSPOR KOPI INDONESIA DI PASAR INTERNASIONAL - Kurnia Subhani; Dompak MT Napitupulu; Mirawati Yanita (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2018)
Coffee is a source of foreign exchange, a source of income for farmers and industrial raw materials producers. This study is aimed to describ competitiveness and to analyze the factors influencing the competitiveness of Indonesian coffee in international markets in Year 1996-2015. The data used was 20 years-time series data. The competitiveness of Indonesian coffee exports in the international market is presented descriptively and the factors that influence the competitiveness of Indonesian coffee in the international market are analyzed by using multiple linear regression models. The results show that Indonesian coffee was competitive both in comparative and competitive in the international market. Coffee export volume and domestic coffee production have a positive effect, while Indonesia's domestic consumption and GDP have a negative effect on the competitiveness of Indonesian coffeeexports in the international market. Increasing competitiveness of Indonesian coffee exports is obtained through increased quality and quantity of coffee production. The increase in export volume can be done through export policies in the form of export subsidies and removing export barriers. The increase in export volume will increase export competitiveness in the international market.